2011
DOI: 10.1186/1471-230x-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Complete response for advanced liver cancer during sorafenib therapy: Case Report

Abstract: BackgroundHepatocellular carcinoma (HCC) is the fifth most common neoplasia in the world. In the past, treatment of advanced HCC with conventional antineoplastic drugs did not result in satisfactory outcomes: recently, in this patient population the oral multikinase inhibitor sorafenib has been able to induce a statistically significant improvement of overall survival. Similarly to other anti-angiogenic drugs employed in other tumour types, also sorafenib seldom induces the dimensional tumour shrinking usually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 22 publications
2
36
1
Order By: Relevance
“…Sorafenib proved to be effective against portal neoplastic thrombosis through the inhibition of the VEGF cascade (29). The partial recanalization of the portal venous system corroborates the hypothesis that sorafenib has a direct action on tumor cells invading the portal system and a modulation effect on the production of pro-thrombotic cytokines by the neoplastic cells (18,30). From the imaging point of view, as also described by other authors (31,32), in the present study a marked response to treatment in a highly enhancing lesion was observed.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Sorafenib proved to be effective against portal neoplastic thrombosis through the inhibition of the VEGF cascade (29). The partial recanalization of the portal venous system corroborates the hypothesis that sorafenib has a direct action on tumor cells invading the portal system and a modulation effect on the production of pro-thrombotic cytokines by the neoplastic cells (18,30). From the imaging point of view, as also described by other authors (31,32), in the present study a marked response to treatment in a highly enhancing lesion was observed.…”
Section: Discussionsupporting
confidence: 77%
“…The partial response (PR) rate in the sorafenib group was 2.0 vs. 1.0% (SHARP) and 3.3 vs. 1.3% (Asia-Pacific) compared with the placebo group (6,7). Only ten case reports of advanced HCC revealing a complete response (CR)/PR to sorafenib monotherapy are present in the literature, published between 2008 and 2011 (Table I) (14)(15)(16)(17)(18)(19). In a multicenter study published in 2014 by Shiba et al, only 18 of 3,047 (0.6%) patients who were administered sorafenib monotherapy at institutions belonging to the Liver Cancer Study Group of Japan obtained a CR (20).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have previously treated a patient with advanced HCC with lung metastasis who achieved CR with sorafenib (29). These results suggest that a number of patients may achieve an objective response with sorafenib therapy (27)(28)(29)(30). However, characteristics of the patients benefiting from, as well as features associated with sorafenib-resistance have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…Sorafenib therapy did not achieve a complete response in 299 patients in the Sorafenib Hepatocellular Carcinoma Assessment Randomized Protocol (SHARP) study or 150 patients in the Asian Pacific study; the partial response rates were 2.0% and 3.3%, respectively (6,7). Only a few studies have reported a complete response in HCC patients receiving sorafenib treatment (8)(9)(10)(11)(12)(13)(14)(15)(16). We listed these in order of the time to cessation (Table).…”
Section: Discussionmentioning
confidence: 99%